Suscetibilidade de fungos nematófagos a fármacos antiparasitários - Vieira, Juliana Nunes (2012)
The rapid development of resistance to gastrointestinal parasites anthelmintics has shown the limited efficiency of this method in the suppression of endoparasitoses in ruminants, and has furthered research in alternative control methods. The use of chemicals in animal anthelmintic treatment, in association with nematophagous fungi used for biological control, is a strategy that has proven to be effective in reducing the nematode population density of farm animals. This study aims to verify the in vitro susceptibility of the nematophagous fungi Arthrobotrys oligospora, Duddingtonia flagrans, Paecilomyces fumosoroseus, Paecilomyces lilacinus, Paecilomyces marquandii and Paecilomyces variotii against the antiparasitic drugs albendazole, thiabendazole, ivermectin (100%), levamisole (7.5%) and closantel (10%) by using the Minimum Inhibitory Concentration (MIC). MICs ranged between 4 and 0,031µg/mL for albendazole, thiabendazole and ivermectin, between 0,937 and 0,117µg/mL for levamisole, and between 0,625 and 0,034 for closantel. The results obtained showed that all antiparasitic drugs tested had an in vitro inhibitory effect on nematophagous fungi, being able to jeopardize the fungus action as a biological control bioagent.